Flexural strength of milled polymer bars, with and without glass fiber reinforcement (Research, Society and Development, 2022)
The aim of this study is to test and compare the flexural strength of milled polymer bars, with and without glass fiber reinforcement. The number of samples in the study was defined through a pilot study on a universal testing machine (EMIC) (n = 5). The brands analyzed in this study were Arch Free Metal, Zantex, Bioplas and PEEK. All samples were submitted to thermal aging before the three-point flexural test. Fracture patterns were analyzed using a Scanning Electron Microscope. Results show that the Arch Free Metal bar presented the largest flexural strength, followed by Zantex and PEEK bars, that lacked statistical difference, and Bioplas bars. Regarding fracture patterns, Arch Free Metal and Zantex bars were partially fractured and showed partial glass fiber rupture; PEEK bars were not fractured and showed plastic behavior; and Bioplas bars were fractured. It is possible to conclude that the reinforced polymer bar Arch Free Metal has a better performance in terms of flexural strength than the other tested materials.